Weighing Cane - (:unkn) unknown (My University, 2009)
A picture of a weighing station where a manual pulley system is used to hoist the harvested cane from the horse-drawn carts onto the scales.
Colour: Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Sugarcane industry; Sugarcane; Scales (Weighing instruments); Carriages and carts; Pulleys